GSM tabanlı katodik koruma SCADA sistemi - (:unkn) unknown (My University, 2008)
İsale hatlarında kullanılan çelik ve ön gerilimli beton boruların katodik korumasının izlenmesi, GSM ve mikroişlemci tabanlı SCADA sistemi ile gerçekleştirilmiştir. Sistem potansiyeli, boru potansiyeli ve anot akımı gibi katodik koruma parametrelerinin manüel yöntemle ölçülmesi yerine, verilerin GSM şebekesi üzerinden ölçülmesi, veritabanında tutulması ve raporlanması sağlanmıştır. Katodik koruma kriterleri, bir kontrol algoritması ile çelik ve ön gerilimli beton borulara uygulanarak, her ölçüm noktası için katodik korumanın olup olmadığı uzaktan tespit edilmiştir. Galvanik katodik koruma yöntemi ile korunan isale hattı, GSM üzerinden gerçek zamanlı olarak takip edilir hale getirilmiştir.

Monitoring cathodic protections of steel and pre-stressed concrete cylinder pipes used in water supplies is realized by a GSM and microprocessor based SCADA system. Instead of using manual methods, automatically measuring the cathodic protection parameters such as system potential, pipe ground potential and anode current over GSM network are successfully achieved. All the relevant data are stored in a database and reported when needed. The whole water supply system is monitored in real-time via GSM. By applying the cathodic protection criteria for steel and pre-stressed concrete cylinder pipes, each measurement point is remotely determined through a control algorithm to check whether the cathodic protection is at satisfactory level.
GSM based cathodic protection SCADA system